Model Problem Solving Untuk Peningkatan Hasil Belajar Siswa Kelas IV Sekolah Dasar - Dita Dwi Astuti; Sumarwiyah Sumarwiyah; Imaniar Purbasari (Peneliti.net, 2020)
Abstract. This study aims to improve student learning outcomes, especially in the realm of knowledge and use problem solving models, problem solving models are needed by students in learning and able to increase student activity, because in problem solving models students are expected to be able to solve existing problems, students are expected to be able to active in learning and not only teachers who are active. The focus in this research in the application of problem solving models to improve learning outcomes. The subjects of this study were students in grade IV SDN 2 Gondoharum, data collection techniques in this study were interviews, observation, tests and documentation. The data validity tests technique used in this study expert judgment. The research subjects were 19 students which lasted for 2 cycles. The percentage of students completeness in the realm of knowledge of Indonesian content in the first cycle was 73,68% and in the second cycle the percentage was 89,47%. In IPS cycle I got a percentage og 78,94% and in the second cycle 89,47%, there was an increase in each cycle it shows that the use of problem solving models can improve student learning outcomes. Keyword: Learning outcomes, model Problem Solving